Implementation of Assertive Training to Increase the Ability of Anger Expression in Violent Behavior Patients at RSMM Bogor - Tjahjanti Kristaningsih; Ani Nuraeni; Hemma Siti Rahayu; Mayang Audi (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2023)
Aim: Violent behavior is a feeling of anger, annoyance, emotion, or disappointment that arises and is characterized by a clenched hand, bulging eyes, glaring, loud, and harshly talk that can result in dangerous actions for himself and others, and the environment. Violent behavior can be caused by various factors, both internal and external. One way to deal with violent behavior is by implementing assertive training. Assertive training is an effort to express anger well so that patients can express their annoyance well, ask for help and apologize well. Method: The case study research design involved four subjects chosen based on established inclusion criteria to obtain an overview of the implementation of assertive exercises in increasing the ability to express anger in patients with violent behavior. Result: The main intervention in this paper is the application of assertive exercises for two subjects. After the intervention was carried out three times a day in five days, the result was an increase in ability in assertive training and in expressing anger in patients with violent behavior who implement assertive training. Two patients who did not implement assertive training still had difficulty controlling their anger properly. Conclusion: This case study concludes that assertive training can increase the ability of angry expressions well, such as expressing annoyance well, asking for help well, and rejecting well.